The Journal of Physiological Sciences - Ishikawa, Yoshihiro; Tominaga, Makoto; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
The Journal of Physiological Sciences publishes peer-reviewed original papers, reviews, short communications, technical notes, and letters to the editor, based on the principles and theories of modern physiology and addressed to the international scientific community. All fields of physiology are covered, encompassing molecular, cellular and systems physiology. The emphasis is on human and vertebrate physiology, but comparative papers are also considered. The process of obtaining results must be ethically sound. Fields covered: Adaptation and environment Autonomic nervous function Biophysics Cell sensors and signaling Central nervous system and brain sciences Endocrinology and metabolism Excitable membranes and neural cell physiology Exercise physiology Gastrointestinal and kidney physiology Heart and circulatory physiology Molecular and cellular physiology Muscle physiology Physiome/systems biology Respiration physiology Senses.
Keywords: Human physiology; Neurosciences; Biochemistry; Neurobiology; Human Physiology; Neurosciences; Animal Biochemistry; Animal Physiology; Cell Physiology; Neurobiology